Faktor-Faktor Yang Berhubungan Dengan Praktik Personal Hygiene Pada Lansia Di Panti Wreda Kota Pekalongan - Clarista Frezharika Ananda; Anik Indriono; Siwi Sri Widhowati (PENA NURSING, 2023)
Background: Old age is the period when living beings are at maturity in size, function and have shown differences from time to time. There are various responses regarding the limits of old age, age as the last stage in the aging process, namely the ages of 60, 65 and 70 years. The aging process is influenced by many factors and is very complex. The increasing population is directly proportional to the health and social welfare problems that arise among the elderly, personal hygiene factors are one of the problems for the elderly population. The behavior of maintaining personal hygiene can be assessed from factors related to personal hygiene, namely social practices, self-choice, body image, socioeconomic status, knowledge and motivation, culture and physical conditions.Methods: This research method was conducted using correlational analytic research methods with a cross sectional approach. The sample in this study were 43 respondents.Results: of this study used linear regression statistical tests. The results of the multivariate test with linear regression showed that the knowledge factor (p-value 0.032) and physical condition (p-value 0.045) had a significant relationship with personal hygiene practices in the elderly with a p value <0.05.